147k views
1 vote
-3(x+n) = x what is x

User Sudara
by
6.5k points

1 Answer

1 vote

Answer:

x = -3n/4

Explanation:

in order to solve for x in this expression we would open the bracket with -3 according to BODMAS rule. then we would evaluate for the value of x

-3(x+n) = x what is x

-3x-3n= x

-3x = x + 3n

-3x -x = 3n

-4x = 3n

divide both sides by the coefficient of x which is -4

-4x/-4 = 3n/-4

x = -3n/4

therefore the value of x in the expression -3(x+n) = x is evaluated to be

x = -3n/4

User Mustafagok
by
5.6k points